Moderating Role of work team Resilience in The Relationship Between Innovation Leadership and Strategic fit on Performance at The University of Yunan, China - Li, Ting; Kerdpitak, Chayanan (Nimitmai Review Journal, 2024)
This study examines the influence of innovation leadership and strategic fit on performance organization: the moderating role of work team resilience at a university in Yunnan, China. The research employs a questionnaire based on a tested conceptual framework, using criteria evaluation, sample selection, and simple random sampling. The study examines the impact of innovation leadership, strategic fit, and work team resilience on high performance using random sampling. Results show differences in academic staff percentages at 2 private Yunnan universities. The study uses 300 samples, an anonymous and confidential survey questionnaire, and simple random sampling. The overall mean score of performance is 0.860, with a Cronbach’s Alpha of 0.915, indicating high dependability. The study found a strong correlation between the quality of education and student success in academic and professional endeavors. The study also found that organizational toughness plays a significant role in the development of team resilience. The study investigates the mediating relationship between work team resilience, performance, innovation leadership, and strategic fit in a university in Yunnan Province, China. The path coefficients and critical ratio CR indicate significant differences at the 0.05 level. The mediation hypothesis describes the mechanism by which an independent variable affects the dependent variable through an intervening variable. The standard path coefficient and p-value are (0.093) and p<0.010, respectively, for innovation leadership, work team resilience, performance, and strategic fit, respectively. Updating educational programs, infrastructure, and human resources is crucial for enhancing performance and societal contributions. The study highlights the importance of strategic fit and work team resilience in enhancing leadership, performance, and community well-being. Incorporating leadership innovation into education helps students develop essential skills such as communication, teamwork, and decision-making, which are crucial for their future success in a globalized and interconnected society.